2006
DOI: 10.1192/bjp.188.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Emergency psychiatry, compulsory admissions and clinical presentation among immigrants to the Netherlands

Abstract: Non-Western immigrant groups were overrepresented in psychiatric emergency care and were admitted compulsorily more frequently, possibly owing to a different clinical presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
60
3
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 10 publications
14
60
3
5
Order By: Relevance
“…In our study, the most common reason for ED admission was psychosis. This is similar to other studies that reported psychotic symptoms as most common among immigrants in emergency departments [17,20]. A systematic review by McGarth et al reported that psychotic episodes are more prevalent among ethnic minority groups [9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the most common reason for ED admission was psychosis. This is similar to other studies that reported psychotic symptoms as most common among immigrants in emergency departments [17,20]. A systematic review by McGarth et al reported that psychotic episodes are more prevalent among ethnic minority groups [9].…”
Section: Discussionsupporting
confidence: 90%
“…As in other studies, we confirm that immigrants have a high rate of compulsory presentation to mental health emergency departments [17,26,27]. In psychiatry, the main clinical examination tool is language, a fact that sometimes raises barriers in care provision.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[28][29][30][31][32][33] Clinician biases about the types of disorders that immigrants experience and misinterpretation of cultural beliefs may lead to overdiagnosis of psychotic disorders and underdiagnosis of affective disorders in high immigrant areas. [25][26][27] While these biases are often discussed regarding ethnic minorities, 28,29,34,35 they may also explain admission patterns in immigrant populations.…”
mentioning
confidence: 99%
“…Individuallevel studies have reported that immigrants are more likely than the host population to be diagnosed with psychotic disorders when experiencing a mood disorder or expressing culturally appropriate emotional symptoms. [24][25][26][27][28] Clinicians may use different decision rules when diagnosing members of immigrant or ethnic groups, likely because of biases or stereotypes. [28][29][30][31][32][33] Clinician biases about the types of disorders that immigrants experience and misinterpretation of cultural beliefs may lead to overdiagnosis of psychotic disorders and underdiagnosis of affective disorders in high immigrant areas.…”
mentioning
confidence: 99%